1997
DOI: 10.1152/jn.1997.77.2.709
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Muscarinic Receptor Subtypes Suppress Excitatory and Inhibitory Synaptic Responses in Cortical Neurons

Abstract: Simultaneous whole cell recordings from monosynaptically connected cortical cells were performed with the use of two patch pipettes to determine the effect of acetylcholine (ACh) on both excitatory and inhibitory postsynaptic potentials (EPSPs and IPSPs, respectively) in cultured neurons from rat visual cortex. For 96% of EPSPs and 73% of IPSPs, ACh potently suppressed postsynaptic potentials in a dose-dependent manner. The estimated effective concentrations to produce half maximal response (EC50S) were 30 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 50 publications
7
87
0
1
Order By: Relevance
“…Cholinergic agonists including ACh and carbachol effectively suppress evoked EPSPs/EPSCs recorded from pyramidal cells in the cerebral cortex (Kimura and Baughman 1997;Levy et al 2009;Murakoshi et al 2001). These studies have provided the evidence that a decrease in EPSP/EPSCs is accompanied by an increase in PPR and are blocked by atropine, suggesting that cholinergic suppression of EPSP/EPSCs is mediated by presynaptic mAChRs.…”
Section: Cholinergic Modulation Of Inhibitory Synapses From Fs/non-fsmentioning
confidence: 98%
See 2 more Smart Citations
“…Cholinergic agonists including ACh and carbachol effectively suppress evoked EPSPs/EPSCs recorded from pyramidal cells in the cerebral cortex (Kimura and Baughman 1997;Levy et al 2009;Murakoshi et al 2001). These studies have provided the evidence that a decrease in EPSP/EPSCs is accompanied by an increase in PPR and are blocked by atropine, suggesting that cholinergic suppression of EPSP/EPSCs is mediated by presynaptic mAChRs.…”
Section: Cholinergic Modulation Of Inhibitory Synapses From Fs/non-fsmentioning
confidence: 98%
“…These suppressive effects of ACh are likely to be mediated by presynaptic mAChRs (Kimura and Baughman 1997;Murakoshi et al 2001), although Levy et al (2006) reported a nicotinic receptor contribution in addition to mAChRs. Similar results were obtained in the case of inhibitory postsynaptic potentials (IPSPs) or currents (IPSCs): thus ACh decreased the amplitude of evoked IPSPs/IPSCs recorded from pyramidal neurons via presynaptic mAChRs (Kimura and Baughman 1997;Xiao et al 2009). Another important role of ACh is modulation of neuronal excitability by depolarizing or hyperpolarizing the resting membrane potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter 1/CV 2 is primarily determined by the presynaptic factors controlling transmitter release. By plotting the ratio of experimental to control 1/CV 2 against the ratio of experimental to control response amplitudes, the dependence of presynaptic versus postsynaptic function can be determined (Bekkers and Stevens, 1990;Manabe et al, 1993;Kimura and Baughman, 1997). A positive correlation between the two was shown to reflect a presynaptic mechanism, whereas a horizontal regression is indicative of a purely postsynaptic action.…”
Section: Regulation Of Long-range Gabaergic Inhibition By Acetylcholinementioning
confidence: 99%
“…In addition to this enhancement of LTP, other eVects may also contribute to setting dynamics in the hippocampus appropriate for encoding information (Hasselmo & Schnell, 1994). In particular, a large body of research has demonstrated the involvement of mAChRs in the regulation of glutamatergic transmission, including suppression of transmission at the SchaVer collateral (SC) synapses in the hippocampus by a presynaptic mechanism ARTICLE IN PRESS (reviewed in Hasselmo, 1999b;Hounsgaard, 1978;Kimura and Baughman, 1997;Levey, 1996;Rasmusson, 2000;Valentino and Dingledine, 1981). Prior research from this laboratory has presented physiological data on ACh suppression (Hasselmo & Fehlau, 2001;Hasselmo & Schnell, 1994;Hasselmo, Schnell, & Barkai, 1995) as well as a neural model of how this suppression may be acting to regulate the dynamics of the hippocampus to enhance pattern separation and facilitate encoding (Hasselmo, 1999a(Hasselmo, , 1999bHasselmo, Bodelon, & Wyble, 2002;Hasselmo & McClelland, 1999;Hasselmo & Schnell, 1994;Hasselmo, Wyble, & Wallenstein, 1996;Wyble, Linster, & Hasselmo, 2000).…”
Section: Introductionmentioning
confidence: 99%